2016
DOI: 10.1086/683645
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Job Displacement on Couples’ Fertility Decisions

Abstract: his paper analyzes the effects of job displacement on fertility using Finnish longitudinal register data. We focus on couples where one spouse has lost a job due to a plant closure and follow them for several years before and following the job loss. The results show that female job loss decreases fertility. For every 100 displaced females, there are three fewer children born. Male job loss has no impact on fertility despite resulting in a stronger decrease in family income than female job loss. This indicates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
75
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 110 publications
(92 citation statements)
references
References 31 publications
(3 reference statements)
7
75
2
Order By: Relevance
“…The small sample sizes also did not allow researchers to conduct more subtle investigations which might have explored group-specific differences. In addition, scholars have expressed concerns that the unemployed population differ from the employed population in many respects (Del Bono et al 2014;Huttunen and Kellokumpu 2015). Thus, the issue of unobserved population heterogeneity was not resolved in these studies (see also Schröder 2010 for a detailed discussion).…”
Section: Economic Uncertainty and Fertility: Recent Evidencementioning
confidence: 99%
“…The small sample sizes also did not allow researchers to conduct more subtle investigations which might have explored group-specific differences. In addition, scholars have expressed concerns that the unemployed population differ from the employed population in many respects (Del Bono et al 2014;Huttunen and Kellokumpu 2015). Thus, the issue of unobserved population heterogeneity was not resolved in these studies (see also Schröder 2010 for a detailed discussion).…”
Section: Economic Uncertainty and Fertility: Recent Evidencementioning
confidence: 99%
“…In order to make the estimated e¤ects of o¤shoring and import competition on employment outcomes comparable, we compute relative e¤ects for an increase equal to the sample mean of the respective measure. An increase equal to the sample mean of o¤shoring to China (the mean 0.45 percent doubles to 0.90 percent) is associated with a -0.69 percent decrease in the probability of being employed in the same …rm in year t + 2: 33 The e¤ect of import competition is largest in the …rst year. An increase equal to the sample mean level of import competition from China (the mean 1.25 doubles to 2.5) is associated with a 1.07 percent decrease in the probability of being employed in the same …rm in year t.…”
Section: Employment Outcomesmentioning
confidence: 98%
“…The …rst-stage es- 33 The percentage e¤ect is computed as -0.011*0.45/0.7152*100=-0.692. The means are reported in Table A2 in Appendix A.…”
mentioning
confidence: 99%
“…They found that higher child risks diminish fertility and consumption while risk aversion speeds up fertility as households use the safe utility derived from a child as insurance against fluctuations in consumption. Also, they found that fertility is increasing in the correlation between income and child cost shocks Huttunen and Kellokumpu (2012) analysed the effects of job displacement (both male and female) on fertility using Finnish longitudinal employer-employee data (FLEED). They found that woman's own job loss decreases fertility mainly for highly educated women.…”
Section: Literature Reviewmentioning
confidence: 99%